Menggali Pembelajaran Terintegrasi Kearifan Lokal: E-book Ekosistem Sendang Made untuk Melatih Kemampuan Berpikir Kritis Siswa Kelas X SMA - Lazulfah Nadhifatul Maulani; Dyah Hariani; Rinie Pratiwi Puspitawati (Jurnal Penelitian Pendidikan IPA, 2024)
This research focuses on developing an integrated e-book that incorporates Sendang Made local wisdom into ecosystem material to enhance high school students' critical thinking skills. The study addresses the challenge of limited teaching materials due to the shortage of teachers capable of preparing suitable content for 21st-century learning, which emphasizes critical thinking and technology use. The Research and Development (R&D) method was employed using the ADDIE framework, encompassing analysis, design, development, implementation, and evaluation stages.nData was collected through validation by two biology lecturers, material experts, and media experts, as well as a readability test. The e-book received high validation scores: 3.73 for presentation, 3.73 for content appropriateness, and 3.54 for language appropriateness. The readability test indicated a level 10, aligning with the cognitive level of grade X high school students, and was categorized as very positive and appropriate. In conclusion, the integrated e-book is highly feasible and valid for enhancing critical thinking skills in grade X high school students, making it an effective tool for 21st-century learning.